2005
DOI: 10.1016/j.foreco.2005.05.059
|View full text |Cite
|
Sign up to set email alerts
|

A model for regional analysis of carbon sequestration and timber production

Abstract: The greenhouse effect is one of our most severe current environmental problems. Forests make up large ecosystems and can play an important role in mitigating the emissions of CO 2 , the most important greenhouse gas. Different management regimes affect the ability of forests to sequester carbon. It is important to investigate in what way we best can use forests to mitigate the greenhouse effect. It is also important to study what effect different actions, done to increase carbon sequestration, have on other of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 35 publications
2
64
1
2
Order By: Relevance
“…Our results showed that implementing management plans to favor carbon sequestration reduce the economic benefits from timber production, and vice-versa, indicating that these objectives are in conflict, which is consistent with previous studies (Backéus et al 2005, Raymer et al 2009, Nepal et al 2012. According to the model's results, with C prices of US$ 10 Mg -1 managing teak plantations for carbon sequestration only is not attractive, because of the high market value of teak timber.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed that implementing management plans to favor carbon sequestration reduce the economic benefits from timber production, and vice-versa, indicating that these objectives are in conflict, which is consistent with previous studies (Backéus et al 2005, Raymer et al 2009, Nepal et al 2012. According to the model's results, with C prices of US$ 10 Mg -1 managing teak plantations for carbon sequestration only is not attractive, because of the high market value of teak timber.…”
Section: Discussionsupporting
confidence: 90%
“…Many forest planning models that incorporate carbon sequestration as optimization criteria have been reported in the literature (Hoen & Solberg 1994, Diaz-Balteiro & Romero 2003, Backéus et al 2005, Díaz-Balteiro & Rodriguez 2006, Pohjola & Valsta 2007, Keles & Baskent 2007, Baskent et al 2008, Bravo et al 2008, Raymer et al 2009, Cao et al 2010). In addition, several models quantifying carbon stored in teak trees have been developed (Cubero & Rojas 1999, Kraenzel et al 2003, Gera et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, younger stands tended to sequester more carbon than older stands did according to the formulation in this study. Backeus et al (2005) showed that total carbon storage increases at a slower rate when a forest matures over time, implying that the carbon flux in a forest ecosystem decreases. Furthermore, Pérez-García et al (2005) showed that when carbon emissions are taken into account, shorter rotations incline to increase total carbon storage.…”
Section: Discussionmentioning
confidence: 99%
“…Different management regimes can affect the amount of carbon sequestrated in forest vegetation and soil by controlling the forest management practices, e.g. by changing rotation lengths or intensifying thinning operations (Backeus et al, 2005;Swanson, 2009). In addition, land use activities and forest ecosystem planning are increasingly considered an option for limiting greenhouse gas concentration in the atmosphere (Hu and Wang, 2008;Kaul et al, 2009) as illustrated by several researches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation